2021
DOI: 10.1021/acs.analchem.0c04658
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide-Reduction-Triggered Spontaneous Photoblinking Cy5 Probe for Nanoscopic Imaging of Mitochondrial Dynamics in Live Cells

Abstract: Mitochondria are highly dynamic organelles with interconnected tubule structures that are sensitive to environmental stress and light illumination. Super-resolution optical imaging of mitochondrial dynamics is of significance for understanding such biological events. Direct stochastic optical reconstruction microscopy has the advantages of a high spatial resolution, low phototoxicity in live-cell imaging, and the capacity to incorporate smart fluorescent probes. However, dSTORM imaging in live cells is challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The study of optical imaging is a subject of fundamental and technological importance in many research fields. Of particular interest is that X-ray imaging becomes one of the most important analytical approaches that has been extensively used for medical diagnosis since the discovery of X-rays by Wilhelm Roentgen in 1895. , Owing to the high penetrating ability of X-rays and the various X-ray absorption in different tissues, medical X-ray imaging offers a powerful tool to visualize the internal biological tissues and structures of patients for disease detection and diagnosis. , This X-ray imaging technique relies on the inherent contrast from different X-ray attenuations in tissues to provide useful information on the structural changes for noninvasive monitoring of the disease process. To date, anatomical organs such as skeleton and lungs are easily detected by X-ray imaging due to their large differences in X-ray absorption among bone, tissue, and air. , However, it is often challenging to identify subtle changes in soft tissues, especially for tiny tumors and blood vessels.…”
mentioning
confidence: 99%
“…The study of optical imaging is a subject of fundamental and technological importance in many research fields. Of particular interest is that X-ray imaging becomes one of the most important analytical approaches that has been extensively used for medical diagnosis since the discovery of X-rays by Wilhelm Roentgen in 1895. , Owing to the high penetrating ability of X-rays and the various X-ray absorption in different tissues, medical X-ray imaging offers a powerful tool to visualize the internal biological tissues and structures of patients for disease detection and diagnosis. , This X-ray imaging technique relies on the inherent contrast from different X-ray attenuations in tissues to provide useful information on the structural changes for noninvasive monitoring of the disease process. To date, anatomical organs such as skeleton and lungs are easily detected by X-ray imaging due to their large differences in X-ray absorption among bone, tissue, and air. , However, it is often challenging to identify subtle changes in soft tissues, especially for tiny tumors and blood vessels.…”
mentioning
confidence: 99%
“…Furthermore, Li et al reported the use of a disulfide-conjugated Cy5 fluorogenic probe ( Mito-SS ) without imaging buffer for dSTORM in live cells imaging, allowing for real-time tracking of mitochondrial fusion, fission, and interconnection processes. 188 This cationic probe could accumulate in the mitochondria by MMP and bind with mitochondria by covalent bonding with the cysteine residues in the membrane proteins. The spontaneous photoblinking activation is triggered by the disulfide reduction, which reduced excess thiols on the protein to free thiol.…”
Section: Small-molecule Fluorogenic Probes For Mitochondrial Srimentioning
confidence: 99%
“…In this case, the ability to evade the use of toxic imaging buffer helped in monitoring the live cell intracellular mitochondrial dynamics at nanoscale resolution for more than 3 min. 178…”
Section: Xanthene- Cyanine- Oxazine- and Bodipy-based Fluorophores Fo...mentioning
confidence: 99%
“…In this context, very recently, our group has presented a smart fluorescent probe designing strategy to assimilate spontaneous-blinking properties in the Cy5 fluorophore unit. 178 Basically, Cy5-based probe MitoSS was rationally designed by incorporating a disulfide-substitution in the probe in such a way (Fig. 17(A)) that the probe can demonstrate spontaneous photoblinking under light irradiation.…”
Section: Cyaninementioning
confidence: 99%
See 1 more Smart Citation